Ministry of Finance Decree No. 382 Of The Year 2018 Amending Decree of the Minister of Finance No. 532 Of The Year 2005 Concerning The Collection Of Amounts on the Account of the Non-commercial Professions Tax Payable By The Physician Or Medical Specialist Who Performs His/Her Work For His/Her Own Account In One Of The Hospitals According To The Provision Of Article (71) Of Income Tax Law No. 91 Of The Year 2005 = وزارة المالية قرار رقم 382 لسنة 2018 بتعديل قرار وزير المالية رقم 532 لسنة 2005 بشأن تحصيل مبلغ تحت حساب ضريبة المهن غير التجارية المستحقة على الطبيب أو الإخصائى الذى يقوم بأداء عمل لحسابه الخاص فى إحدي المستشفيات طبقاً لحكم المادة (71) من قانون الضريبة على الدخل رقم 91 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic